Eine Reise von Hermupolis in Oberägypten nach Antiochia in Syrien zur Zeit Kaiser Konstantins - Kirsten, Ernst (ERDKUNDE, 1959)
The 'Archive of Theophanes', on papyrus, in the John Rylands Library, Manchester, conserves in a note-book the description of a journey from Egypt to Syria between 317 and 323 A. C, one decade before the beginning of Christian Pilgrimage to Palestine. By its content the private character of most of the Roman Itineraries and Road-Maps is confirmed; some of the road-stations are identified, and the papyrus is also a valuable contribution to the historical Economic Geography and to historical Botanies of the Holy Land (relating to the maturity of its fruits).